Human METTL12 is a mitochondrial methyltransferase that modifies citrate synthase. Issue 12 (27th April 2017) - Rhein, Virginie F.; Carroll, Joe; Ding, Shujing; Fearnley, Ian M.; Walker, John E.
Abstract : The protein methylome in mammalian mitochondria has been little studied until recently. Here, we describe that lysine‐368 of human citrate synthase is methylated and that the modifying enzyme, localized in the mitochondrial matrix, is methyltransferase‐like protein 12 (METTL12), a member of the family of 7β‐strand methyltransferases. Lysine‐368 is near the active site of citrate synthase, but removal of methylation has no effect on its activity. In mitochondria, it is possible that some or all of the enzymes of the citric acid cycle, including citrate synthase, are organized in metabolons to facilitate the channelling of substrates between participating enzymes. Thus, possible roles for the methylation of Lys‐368 are in controlling substrate channelling itself, or in influencing protein–protein interactions in the metabolon. Abstract : Read the Commentary on this article at doi:10.1002/1873-3468.12692